2007
DOI: 10.1021/es0619253
|View full text |Cite
|
Sign up to set email alerts
|

Ex Situ Aqueous Mineral Carbonation

Abstract: The U.S. Department of Energy's National Energy Technology Laboratory (NETL) located in Albany, OR (formerly the Albany Research Center) has studied ex situ mineral carbonation as a potential option for carbon dioxide sequestration. Studies focused on the reaction of Ca-, Fe-, and Mg-silicate minerals with gaseous CO2 to form geologically stable, naturally occurring solid carbonate minerals. The research included resource evaluation, kinetic studies, process development, and economic evaluation. An initial cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
396
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 488 publications
(448 citation statements)
references
References 8 publications
10
396
0
3
Order By: Relevance
“…In these scenarios, the sequestration facilities should be placed close to the mining sites (Huijgen et al, 2007). Grinding of minerals has been reported to consume the largest energy among the mineral processing processes (Gerdemann et al, 2007). Figure 1.3 shows the grinding energy required for size reduction for the case of wollastonite particles (Gerdemann et al, 2007) using a ball mill and stirred media detritor (SMD).…”
Section: Mineral Co 2 Sequestrationmentioning
confidence: 99%
See 4 more Smart Citations
“…In these scenarios, the sequestration facilities should be placed close to the mining sites (Huijgen et al, 2007). Grinding of minerals has been reported to consume the largest energy among the mineral processing processes (Gerdemann et al, 2007). Figure 1.3 shows the grinding energy required for size reduction for the case of wollastonite particles (Gerdemann et al, 2007) using a ball mill and stirred media detritor (SMD).…”
Section: Mineral Co 2 Sequestrationmentioning
confidence: 99%
“…Grinding of minerals has been reported to consume the largest energy among the mineral processing processes (Gerdemann et al, 2007). Figure 1.3 shows the grinding energy required for size reduction for the case of wollastonite particles (Gerdemann et al, 2007) using a ball mill and stirred media detritor (SMD). It can be observed that reducing the mineral size from 35 μm to 15 μm can greatly influence the process costs by doubling the energy consumption.…”
Section: Mineral Co 2 Sequestrationmentioning
confidence: 99%
See 3 more Smart Citations